Modeling and experimental analysis of wheel-work interface in the cylindrical plunge grinding process - Tawfeek, Tarik (International Journal of Engineering and Technology, 2014)
This paper presents a study of grinding wheel-workpiece interference in external cylindrical plunge grinding processes. This is to study the effect of workpiece surface memory on the workpiece roundness error after grinding. The study has been carried out theoretically on a model simulating cylindrical grinding process. The model takes contact stiffness, grinding wheel and workpiece wear into consideration. The proposed model was sued to predict the normal grinding forces in cylindrical grinding as a function of the previous height and number of waves of the initial profile.The new model has been validated by conducting experiments on a cylindrical grinding machine. Results indicate that the proposed model shows a good agreement with the experimental data obtained.The results of experiments indicate that the proposed modeling method is both feasible and reliable. The results showed that the theoretical model was effective studying the output of cylindrical grinding process. Normal grinding force, vibration level, and roundness error in cylindrical plunge grinding processes are dependent on the workpiece surface memory. Keywords: Plunge Grinding, Modeling, Roundness Error, Surface Memory.